Corporate reorganisation of China's listed companies: Winners and losers - ZHANG, Zinian (Institutional Knowledge at Singapore Management University, 2016)
This article is the first empirical study investigating the corporate reorganisation of Chinese domestically-listed companies. Through examining these cases, it challenges the assertion made by most of these corporate reorganisation plans and by Chinese state-run media reports that creditors and general public shareholders were the major beneficiaries. Through an analysis of the data generated from all forth-three such cases, this articles reveals that: First, unsecured creditors could have, on average, received 61.37% more of their claims if the fundamental value distribution principle, the absolute priority norm, could have been complied with in these reorganisations; Second, if the general-public-shareholder-protection scheme issued by the China Supreme People's Court could be rigorously implemented, 85.37% of the shares relinquished by general public shareholders could have been avoided. These two groups were not the winners. Instead, this article argues that it was local governments and controlling shareholders who were the real winners.